Espaços residenciais fechados em Feira de Santana (1987-2018): uma análise do direito à cidade - Figueredo, Albetania Alvim de (2019)
In recent years, Closed Residential Spaces (CRS) have presented themselves as a solution to some urban problems, especially those related to security, and have won the support and interest of society, being synonymous with quality of life and well being. Nevertheless, when not properly planned, the implementation of this kind of project compromises the full exercise of the right to the city, understood here as a result of a continuous process of combat to the effects of the alienation and domination, put by the hegemony of the unique thought of realization of the life in society. This study investigates how the implementation of the CRS may interfere in the realization of the right to the city. The study area is the city of Feira de Santana (BA), in which 184 of such residential spaces were built from 1987 to 2018. In order to proceed with the study, after the initial contextualization of the problem and exposition of the methodological procedures of the research, a discussion about the concept of right to the city is then undertaken. After that, the legal and urbanistic aspects related to the CRS are exposed. Next, using the collected data, a study of the social and urbanistic impacts of the CRS in Feira de Santana, and, more generally, in Brasil, is undertaken.